Cerebellar neuromodulation improves naming in post-stroke aphasia. Issue 2 (9th November 2020) - Sebastian, Rajani; Kim, Ji Hyun; Brenowitz, Rachel; Tippett, Donna C; Desmond, John E; Celnik, Pablo A; Hillis, Argye E
Abstract: Transcranial direct current stimulation has been shown to increase the efficiency of language therapy in chronic aphasia; however, to date, an optimal stimulation site has not been identified. We investigated whether neuromodulation of the right cerebellum can improve naming skills in chronic aphasia. Using a randomized, double-blind, sham-controlled, within-subject crossover study design, participants received anodal cerebellar stimulation ( n  = 12) or cathodal cerebellar stimulation ( n  = 12) + computerized aphasia therapy then sham + computerized aphasia therapy, or the opposite order. There was no significant effect of treatment (cerebellar stimulation versus sham) for trained naming. However, there was a significant order x treatment interaction, indicating that cerebellar stimulation was more effective than sham immediately post-treatment for participants who received cerebellar stimulation in the first phase. There was a significant effect of treatment (cerebellar stimulation versus sham) for untrained naming immediately post-treatment and the significant improvement in untrained naming was maintained at two months post-treatment. Greater gains in naming (relative to sham) were noted for participants receiving cathodal stimulation for both trained and untrained items. Thus, our study provides evidence that repetitive cerebellar transcranial direct stimulation combined with computerized aphasia treatment can improve picture naming in chronic post-stroke aphasia. These findings suggest that the right cerebellum might be an optimal stimulation site for aphasia rehabilitation and this could be an answer to handle heterogeneous participants who vary in their size and site of left hemisphere lesions. Abstract : Using a randomized, double-blind, sham-controlled, within-subject crossover study design, Sebastian et al. investigated whether cerebellar transcranial direct current stimulation combined with computerized aphasia treatment can improve picture naming in chronic aphasia. Results indicate significant improvement in untrained naming and trained naming (only for participants who received stimulation first) compared to sham. Graphical Abstract: